Entrepreneurial Practices of Coffee Farmers in Bener Meriah, Aceh Province - Musri, Muhammad Khalis; Romano, Romano; Kasimin, Suyanti (Indonesian Journal of Multidisciplinary Science, 2025)
This research examines the entrepreneurial behavior of coffee farmers in Bener Meriah Regency, Aceh Province, Indonesia. Employing a quantitative design, data were collected from 100 farmers through structured questionnaires and semi-structured interviews, and subsequently analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate that both individual characteristics and the business environment significantly influence entrepreneurial behavior, with the business environment exerting the strongest effect. Farmers’ entrepreneurial behavior was generally categorized as high, reflected in dimensions such as innovativeness, risk-taking, persistence, and independence. Conversely, individual and environmental factors were assessed at a moderate level, suggesting that institutional and structural support remain limited. The study highlights the importance of strengthening extension services, market access, financial facilities, and farmer organizations to enhance entrepreneurial capacity and ensure the sustainability of coffee farming systems. These findings provide empirical evidence on the dynamics of entrepreneurial behavior in rural agribusiness contexts and offer policy insights for promoting competitiveness in Indonesia’s coffee sector.